2002
DOI: 10.1097/00000374-200208001-00013
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Rat Alcohol Drinking Behavior Depends on the Age of Drinking Onset

Abstract: Alcohol drinking behavior in experimental animals depends on the age of alcohol drinking onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Ethanol intake (g/kg) over the fourteen sessions was consistently higher for adolescent animals when compared to adults. These data are in accordance to earlier findings showing that adolescent rats consumed more alcohol during 24-hour access sessions Doremus et al, 2005;Lancaster et al, 1996;Yoshimoto et al, 2002). However, others have found that increased intake is only observed when female adolescents are compared to adults and not between male adults and adolescents (Siciliano and Smith, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Ethanol intake (g/kg) over the fourteen sessions was consistently higher for adolescent animals when compared to adults. These data are in accordance to earlier findings showing that adolescent rats consumed more alcohol during 24-hour access sessions Doremus et al, 2005;Lancaster et al, 1996;Yoshimoto et al, 2002). However, others have found that increased intake is only observed when female adolescents are compared to adults and not between male adults and adolescents (Siciliano and Smith, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that attempts to delay onset of use may not influence later addiction. However, in rats which, in contrast to humans, age at onset can be experimentally manipulated, an association has been reported between early exposure to alcohol and subsequent greater daily intake [73], suggesting that the harmful effects of substance exposure may be greater in younger animals. Greater insight into these mechanisms is needed in humans.…”
Section: Age At Onsetmentioning
confidence: 97%
“…Results from rodent studies suggest that age‐related biological factors may be involved in the propensity toward alcohol consumption. One possible mechanism is an age‐related decrease in alcohol‐induced release of dopamine and serotonin in specific areas of the brain associated with reward, such as the nucleus accumbens 63. Yet another possibility is that alcohol may have a greater stimulatory effect on the hypothalamic‐pituitary‐adrenal (HPA) axis in younger animals compared to older animals, resulting in increased circulating levels of glucocorticoids, which are known to potentiate alcohol reward and reinforcement 64,65.…”
Section: Potential Etiological Mechanisms: Genetic and Environmental mentioning
confidence: 99%